2003
DOI: 10.1046/j.1365-2567.2003.01574.x
|View full text |Cite
|
Sign up to set email alerts
|

Roles for CD40, B7 and major histocompatibility complex in induction of enhanced immunity by cryptococcal polysaccharide‐pulsed antigen‐presenting cells

Abstract: SUMMARYImmunization of mice with activated antigen-presenting cells (APC) pulsed ex vivo with cryptococcal capsular polysaccharide, a glucuronoxylomannan (GXM-APC) results in prolongation of survival and delayed-type hypersensitivity (DTH) responsiveness following infection with Cryptococcus neoformans (NU-2). GXM-APC has both non-specific and GXM-specific effects that influence the immune responses that develop in mice after infection with NU-2. Type 1 cytokine responses are augmented after immunization with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…We identified poor proportional monocyte recruitment to the circulating pool of the CSF cells and a predominant non-protective M2 response in most of the autopsy specimens, as well as an inability to phagocytose the fungus in situ. This is consistent with our recent data demonstrating the presence of a STAT5 phosphorylation-blocking GM-CSF autoantibody in a subset of patients with cryptococcal disease [ 25 , 60 ] and suggest that future targeted studies should focus on the mechanistic assessment of cells of myeloid lineage, including evaluation of phagocytosis [ 61 ], oxidative burst [ 62 ]and antigen processing [ 63 ] important to cryptococcal defense. In conclusion, the present study suggests that an ineffective macrophage response in the setting of intact T-cell activation has the potential to cause increased susceptibility of the patient to the fungus and severe CNS disease after initiation of effective anti-fungal therapy.…”
Section: Discussionsupporting
confidence: 90%
“…We identified poor proportional monocyte recruitment to the circulating pool of the CSF cells and a predominant non-protective M2 response in most of the autopsy specimens, as well as an inability to phagocytose the fungus in situ. This is consistent with our recent data demonstrating the presence of a STAT5 phosphorylation-blocking GM-CSF autoantibody in a subset of patients with cryptococcal disease [ 25 , 60 ] and suggest that future targeted studies should focus on the mechanistic assessment of cells of myeloid lineage, including evaluation of phagocytosis [ 61 ], oxidative burst [ 62 ]and antigen processing [ 63 ] important to cryptococcal defense. In conclusion, the present study suggests that an ineffective macrophage response in the setting of intact T-cell activation has the potential to cause increased susceptibility of the patient to the fungus and severe CNS disease after initiation of effective anti-fungal therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The authors concluded that during this process, GXM-dependent and GXM-independent effects occurred. GXM-specific effects were dependent on MHC class II, while GXM independent effects required B7-1 and B7-2 molecules (Blackstock, 2003). …”
Section: Section C Capsule Functions In C Neoformans the Capsule Asmentioning
confidence: 99%
“…DTH analyses were included in our study because the DTH reaction is known to correlate with protective immunity when combined with mononuclear infiltrates and elevated IFN-␥ levels in DTH reaction sites (18). In addition, high IFN-␥ levels without DTH responses do not provide protective immunity to mice infected with C. neoformans (19,20). Results of these studies revealed that IL-4 was needed for development of strong DTH responses after primary infection with both cryptococcal isolates, and IL-4 deficiency did not increase survival of mice undergoing a primary infection with either isolate.…”
mentioning
confidence: 99%